Deep-LUMEN assay – human lung epithelial spheroid classification from brightfield images using deep learning. Issue 24 (5th November 2020) - Abdul, Lyan; Rajasekar, Shravanthi; Lin, Dawn S. Y.; Venkatasubramania Raja, Sibi; Sotra, Alexander; Feng, Yuhang; Liu, Amy; Zhang, Boyang
Abstract : Deep-learning uncovered measurement of epithelial networks (Deep-LUMEN) is an open-source algorithm that can automatically uncover subtle differences in lung alveolar epithelial spheroid morphology from brightfield images. Abstract : Three-dimensional (3D) tissue models such as epithelial spheroids or organoids have become popular for pre-clinical drug studies. In contrast to 2D monolayer culture, the characterization of 3D tissue models from non-invasive brightfield images is a significant challenge. To address this issue, here we report a deep-learning uncovered measurement of epithelial networks (Deep-LUMEN) assay. Deep-LUMEN is an object detection algorithm that has been fine-tuned to automatically uncover subtle differences in epithelial spheroid morphology from brightfield images. This algorithm can track changes in the luminal structure of tissue spheroids and distinguish between polarized and non-polarized lung epithelial spheroids. The Deep-LUMEN assay was validated by screening for changes in spheroid epithelial architecture in response to different extracellular matrices and drug treatments. Specifically, we found the dose-dependent toxicity of cyclosporin can be underestimated if the effect of the drug on tissue morphology is not considered. Hence, Deep-LUMEN could be used to assess drug effects and capture morphological changes in 3D spheroid models in a non-invasive manner.